Integrating answer set programming and constraint logic programming - Mellarkod, Veena S.; Gelfond, Michael; Zhang, Yuanlin (Annals of mathematics and artificial intelligence, 2008)
We introduce a knowledge representation language extending the syntax and semantics of ASP and CR-Prolog, give some examples of its use, and present an algorithm, , for computing answer sets of programs. The algorithm does not require full grounding of a program and combines “classical” ASP solving methods with constraint logic programming techniques and CR-Prolog based abduction. The based approach often allows to solve problems which are impossible to solve by more traditional ASP solving techniques. We believe that further investigation of the language and development of more efficient and reliable solvers for its programs can help to substantially expand the domain of applicability of the answer set programming paradigm.